How do we learn about improving health care: a call for a new epistemological paradigm - Massoud, M. Rashad; Barry, Danika; Murphy, Andrew; Albrecht, Yvonne; Sax, Sylvia; Parchman, Michael (International journal for quality in health care, 2016)
AbstractPurpose. The field of improving health care has been achieving more significant results in outcomes at scale in recent years. This has raised legitimat
Gesehen am 13.05.2020